Mortality Results from a Randomized Prostate-Cancer Screening Trial - Andriole, Gerald L; Crawford, E. David; Grubb, Robert L; Buys, Saundra S; Chia, David; Church, Timothy R; Fouad, Mona N; Gelmann, Edward P; Kvale, Paul A; Reding, Douglas J; Weissfeld, Joel L; Yokochi, Lance A; et al. (The New England journal of medicine, 2009)
In this study involving nearly 77,000 men, investigators analyzed the effect of screening with prostate-specific–antigen testing and digital rectal examination on the rate of death from prostate cancer, as compared with usual care. After a follow-up of 7 years, the death rates from prostate cancer did not differ significantly between the two study groups. Data from the 10-year follow-up (which were 67% complete) also showed no significant difference in prostate-cancer mortality. The benefit of screening for prostate cancer with serum prostate-specific–antigen (PSA) testing, digital rectal examination, or any other screening test is unknown. There has been no comprehensive assessment of the trade-offs between benefits and risks. Despite these uncertainties, PSA screening has been adopted by many patients and physicians in the United States and other countries. The use of PSA testing as a screening tool has increased dramatically in the United States since 1988. 1 Numerous observational studies have reported conflicting findings regarding the benefit of screening. 2 As a result, the screening recommendations of various organizations differ. The American Urological Association and . . .